Sarcopenia is a prognostic factor in living donor liver transplantation - Masuda, Toshiro; Shirabe, Ken; Ikegami, Toru; Harimoto, Norifumi; Yoshizumi, Tomoharu; Soejima, Yuji; Uchiyama, Hideaki; Ikeda, Tetsuo; Baba, Hideo; Maehara, Yoshihiko (Liver transplantation, 2014)
The aims of this study were to investigate sarcopenia as a novel predictor of mortality and sepsis after living donor liver transplantation (LDLT) and to evaluate the effects of early enteral nutrition on patients with sarcopenia. Two hundred four patients undergoing preoperative computed tomography within the month before LDLT were retrospectively evaluated. The lengths of the major and minor axes of the psoas muscle were simply measured at the caudal end of the third lumbar vertebra, and the area of the psoas muscle was calculated. A psoas muscle area lower than the 5th percentile for healthy donors of each sex was defined as sarcopenia. Ninety‐six of the 204 patients (47.1%), including 58.3% (60/103) of the male patients and 35.6% (36/101) of the female patients, were diagnosed with sarcopenia. Sarcopenia was independently and significantly associated with overall survival: there was an approximately 2‐fold higher risk of death for patients with sarcopenia versus patients without sarcopenia (hazard ratio = 2.06, P = 0.047). Sarcopenia was an independent predictor of postoperative sepsis (hazard ratio = 5.31, P = 0.009). Other independent predictors were a younger recipient age (P < 0.001) and a higher body mass index (P = 0.02). Early enteral nutrition within the first 48 hours after LDLT was performed for 24.2% in 2003‐2007 and for 100% in 2008‐2011, and the incidence of postoperative sepsis for patients with sarcopenia (n = 96) was 28.2% (11/39) in 2003‐2007 and 10.5% (6/57) in 2008‐2011 (P = 0.03). In conclusion, sarcopenia is an independent predictor of mortality and sepsis after LDLT. The incidence of postoperative sepsis was reduced even in patients with sarcopenia after the routine application of early enteral nutrition. Liver Transpl 20:401–407, 2014. © 2013 AASLD.